The Preclinical Properties of a Novel Group II Metabotropic Glutamate Receptor Agonist LY379268 - Imre, Gabor (CNS Drug Rev, 2007)
Activation of group II metabotropic glutamate (mGlu2/3) receptors reduces excessive glutamate release that is often associated with neurodegenerative and psychiatric disorders. This finding encouraged the search for potent and selective agonists as potential therapeutic agents. The search led to the discovery of LY379268 {(‐)‐2‐oxa‐4‐aminobicyclo[3.1.0]hexane‐4,6‐dicarboxylic acid}, which is a highly potent and systemically available mGlu2/3 receptor agonist. LY379268 was effective in several animal models of stroke, epilepsy, drug abuse, schizophrenia, and pain. Suppression of motor activity is the major side effect of LY379268. Upon repeated administration tolerance develops to this side effect, while the therapeutic effects of LY379268 remain. To date, no clinical data with LY379268 are available. This review article summarizes the preclinical pharmacology of LY379268.